Intensitas Ganoderma boninense Pada Kelapa Sawit Fase TM di Lahan Tadah Hujan Perkebunan Rakyat Sungai Dua Dusun XII - Anggraini, Sari; Kho, Robert; Parinduri, Zahratul Mina; Hia, Krisman; Tarigan, Dicky Brema (UNIVERSITAS LABUHANBATU, 2025)
Ganoderma boninense is a soil-borne pathogenic fungus responsible for basal stem rot (BSR) disease in oil palm (Elaeis guineensis Jacq.), which significantly reduces palm productivity. This study investigates the intensity of Ganoderma boninense in oil palm trees at the mature or productive stage grown on rainfed land with monoculture and polyculture planting pattern. The research was conducted through field observations and random purposive sampling across several plantation blocks. Disease intensity was determined based on disease incidence and severity using standard assessment scales. Results showed a range of disease intensities, influenced by plant age, soil conditions, drainage, and plantation sanitation practices. The highest disease intensity occurred in older palm stands with poor water management and lack of disease control efforts. The findings indicate that Ganoderma boninense remains a serious threat to oil palm cultivated in rainfed areas. Effective early detection and integrated disease management strategies are essential to reduce yield losses and maintain sustainable oil palm production under rainfed conditions. Keywords: ganoderma boninense, basal stem rot, oil palm, disease intensity, rainfed land